Association between physical fitness and cognitive performance in 19-24 year old males - Esmailzadeh, Samad; Hartman, Esther; Farzizadeh, Reza; Azevedo, Liane B.; Kalantari, Hassan-Ali; Dziembowska, Inga; Kostencka, Alicja; Narimani, Mohammad; Abravesh, Akbar (Biology of Sport, 2018)
The present study aimed to explore the association between physical fitness (PF) and cognitive performance in a sample of 19-24 year old males. Two hundred and eleven young males (20.2±1.5 years) participated in the study. Cognitive functioning tasks including information processing speed and inhibitory control were measured in addition to PF and motor fitness components such as aerobic fitness, static strength, explosive strength, agility and speed. Regression analysis showed that after adjustment for potential confounders (e.g. age, socioeconomic status, adiposity and physical activity), aerobic fitness (represented by shorter time in the one-mile run) was positively associated with composite inhibitory control scores (standardized β=0.17; p=0.04) and negatively associated with Δ Simon (standardized β= -0.21; p=0.04). Explosive strength was negatively associated with composite information processing scores (standardized β= -0.24; P=0.01), and composite inhibitory control scores (standardized β= -0.22; p=0.02). Speed of movement, agility and static strength were not associated with any of the cognitive tests. In conclusion, aerobic fitness and explosive strength but not speed, agility or static strength might be indicators of underlying cognitive functioning tasks in 19-24 year old males.